2020
DOI: 10.1200/jco.2020.38.15_suppl.e19325
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient cancer rehabilitation to improve patient reported and objective measures of function.

Abstract: e19325 Background: Adults with cancer often struggle with persistent symptoms that negatively impact quality of life (QoL), physical and social function. Cancer rehabilitation delivered by a trained physical and/or occupational therapist (PT/OT) is recommended. However, evidence is lacking regarding the impact of community-based PT/OT on patients' functioning. Methods: We assessed adults (≥ 18 years) who completed cancer-specific visits in routine care at two outpatient rehabilitation clinics. Demographic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Previous authors have suggested that hybrid models may enhance a cancer survivor's ability to maintain appointments by reducing barriers to rehabilitation, including transportation restrictions, inclement weather, illness, anxiety, and depression, and time constrictions due to work or other responsibilities [28,45,46]. In our study, the survivors in the hybrid group attended more visits over a longer period, suggesting that having the option of telerehabilitation may have enhanced the accessibility of services by minimizing the barriers.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Previous authors have suggested that hybrid models may enhance a cancer survivor's ability to maintain appointments by reducing barriers to rehabilitation, including transportation restrictions, inclement weather, illness, anxiety, and depression, and time constrictions due to work or other responsibilities [28,45,46]. In our study, the survivors in the hybrid group attended more visits over a longer period, suggesting that having the option of telerehabilitation may have enhanced the accessibility of services by minimizing the barriers.…”
Section: Discussionmentioning
confidence: 50%
“…The limited ability to control for all the potential confounding variables is another important limitation of this study. We included the available covariates in the main effects analyses, although additional variables could be investigated in future studies, including diagnosis stage and treatment type and status [46], patient digital literacy and confidence [19,20], and the therapist's experience with telerehabilitation [16,26]. We recommend future studies to capture these additional covariates to better understand how they may, or may not, influence the effectiveness of rehabilitation interventions.…”
Section: Limitationsmentioning
confidence: 99%